1985
DOI: 10.1080/03601238509372501
|View full text |Cite
|
Sign up to set email alerts
|

Presence and biomagnification of organochlorine pollutants and heavy metals in mammals of doñana national park (Spain), 1982–1983

Abstract: The existence of 11 organochlorine compounds and five heavy metals in the liver and muscle of 57 members of 10 species of mammals, all from Doñana National Park (Spain), has been investigated. Five organochlorine compounds have been found and the five heavy metals were present in the samples. The biomagnification of organochlorines is shown. The detected concentrations for each trophic rank seem not to influence unfavourably on the population stability of the species. The rabbit is proposed as a monitor specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
7
1
1

Year Published

1995
1995
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 13 publications
3
7
1
1
Order By: Relevance
“…In Spain, DDT concentrations of 0.8 g/g fat basis in otter (Lutra lutra) muscle (Hernandez et al 1985) are similar to our results. In 1986, higher values (18.5 g/g) were reported for otters in Great Britain (Mason et al 1986).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In Spain, DDT concentrations of 0.8 g/g fat basis in otter (Lutra lutra) muscle (Hernandez et al 1985) are similar to our results. In 1986, higher values (18.5 g/g) were reported for otters in Great Britain (Mason et al 1986).…”
Section: Discussionsupporting
confidence: 93%
“…Our data reveal that tissues of red foxes living in the provinces of Siena, Pisa, and in the Maremma Natural Park (Grosseto) are moderately contaminated by HCB-and DDT-based pesticides; they contain high PCB levels. This finding is in line with data concerning other European carnivores such as the Arctic fox (Norheim 1978), the polar bear (Norheim et al 1992), and the otter (Hernandez et al 1985;Mason et al 1986). Mean PCB values in the muscle of foxes were approximately 20 ppm (fat basis) near Siena, 40 ppm in the Maremma Natural Park, and 7 ppm near Pisa.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our data on cadmium occurrence in WB meat fell within the range of published data, i.e., between 0.001 and 0.355 mg kg -1 ww (Medvedev 1999;Rudy 2010;Taggart et al 2011). Compared with the data presented by Hernández et al (1985) regarding wild Spanish fauna, we observed lower levels of cadmium contamination in WB meat (geometric means of 0.07 vs. 0.12 mg kg -1 ww) as well as WB liver (geometric means of 0.067 vs. 0.45 mg kg -1 ww). Our data regarding cadmium in WB liver also differs from data published by Wolkers et al (1994), who reported a median cadmium concentration as high as 2.05 mg kg -1 dry weight (dw) in liver samples of WBs age 1.5-5 years.…”
Section: /2006 For Pigs and Other Farmed Species (European Commissupporting
confidence: 86%
“…The literature dealing with heavy-metal contamination of game meat (Hernández et al 1985;Swiergosz et al 1993;Falandysz 1994;Wolkers et al 1994;Kottferová and Koréneková 1998;Guitart et al 2002;Lord et al 2002;Falandysz et al 2005;Lazarus et al 2008) highlights that heavy metals can reach concentration levels high enough to make some of these products unsafe for human consumption. Wild ungulate populations are increasing throughout Europe (Saez-Royuela and Telleria 1986;DelibesMateos et al 2009;Meriggi et al 2011).…”
mentioning
confidence: 99%